Tourism and hospitality marketing - Buenaventura, John Paul; Gutierrez, Liberty Buenaventura- (Manila : Mindshapers Co., Inc., 2022)
The aim of this book is to provide students with an understanding of the key concepts and practices of marketing that are applied in the tourism and hospitality industries.
Chapter .1 Introduction to marketing -- Chapter 2. Hospitality services marketing -- Chapter 3. Hospitality marketing mix -- Chapter 4. Product service mix -- Chapter 5. Price mix -- Chapter 6. Promotion mix -- Chapter 7. Place mix-channel of distribution -- Chapter 8. Marketing plan -- Chapter 9. Strategic marketing and tactical marketing -- Chapter 10. Market opportunity and consumer analysis -- Chapter 11. Consumer behavior -- Chapter 12. Customer relationship development strategies -- Chapter 13. Marketing research and environment -- Chapter 14. Market segmentation -- Chapter 15. Tourism marketing.
Includes bibliographical references
Keywords: TOURISM -- MANAGEMENT; HOSPITALITY INDUSTRY -- MANAGEMENT